Clinical Features Associated with 'Normal Range' Fibrin D-Dimer Levels in Atrial Fibrillation Patients with Left Atrial Thrombus. (December 2022) - Bai, Ying; Luo, Si-Qing; Liu, Si-Tong; Gong, Ling; Zhong, Peng; Wang, Zhen-Zhou; Lip, Gregory YH; Zou, Yi-Xi; Guo, Wei-Hua
Background: Left atrial thrombus (LAT) often complicates with atrial fibrillation (AF). The evidence whether fibrin D-dimer levels could be used as a predictive biomarker for LAT is contradictory. This study firstly investigated the relationship between 'normal range' D-dimer and prevalent LAT. Second, we explored factors contributing to normal D-dimer levels in the presence of LAT. Methods: We studied 244 AF patients with LAT (mean age: 59.9 years, SD:11.7; 53.3% female): of these, 103 (42.2%) had normal D-dimer, 25 (10.2%) had atrial thrombus exclusion score (ATE score) of 0 19 (16.7%) males had CHA2 DS2 -VASc score of 0, 21(16.2%) females had CHA2 DS2 -VASc score of 1 and 16 had overlapped ATE score of 0 and CHA2 DS2 -VASc score of 0 (N = 8 if male) or CHA2 DS2 -VASc score of 1(N = 8 if female). Using multivariate binary analysis, larger left atrial diameter (LAD; adjusted OR: 1.06, 1.03−1.10, p = 0.001) were associated with increased D-dimer. Patients with high body mass index (BMI), hypertension history and previous anticoagulation were more likely to show normal range D-dimer levels in the presence of LAT. Conclusions: A high prevalence (42.2%) of 'normal range' D-dimer levels was found in AF patients with LAT, especially in those with hypertension, high BMI and prior anticoagulation. D-dimer levels of those patients with larger LAD were more likely to be increased.